Metabolizable Energy Content of Meat and Bone Meal in Corn-Soybean Meal or Corn, Wheat and Soybean Meal Diets for Broilers - Oluyinka A. Olukosi; Olayiwola Adeola (The Journal of Poultry Science, 2010)
The experiment was conducted to determine the apparent metabolizable energy (AME) or nitrogen-corrected metabolizable energy (AMEn) content of a high protein meat and bone meal (MBM) in broiler diets contain graded levels of wheat. Two hundred eighty-eight 14-d old broilers were allocated to six dietary treatments in a randomized complete block design and a2×3 factorial arrangement of treatments namely two levels of MBM (0 and 80g/kg) and three levels of wheat (0, 100 and 200g/kg). Wheat replaced part of corn and soybean meal and MBM was added at 0 or 80g/kg at each level of wheat. The birds received the diets for 7 d, and excreta were collected on d 19 to 21. The substitution of corn and SBM by wheat (200g/kg) increased the total NSP content in the diet by 11g/kg. There was a 5% decrease in both AME and AMEn when the level of wheat in the corn-SBM was increased to 200g/kg but this decrease was not significant. On the average, irrespective of wheat levels, AME and AMEn of the MBM were 2,734 and 2,586kcal/kg, respectively. Dietary AME and AMEn were greater in the diets with 200g/kg wheat compared to corn-SBM diet (P<0.05), and N excretion was greater (P<0.01) in the diets with MBM. Our results suggest that replacing part of corn and soybean meal with up to 200g/kg of wheat similar to what was used in the current study would have no effect on metabolizable energy of MBM.